How Social Media Promotion Desentralization: Study on Indonesian Ministry of Internal Affairs Twitter Accounts? - Muchamad Difa, Fredyan Davice; Laila Mantu, Indri Nur; Nurmandi, Achmad; Loilatu, Mohammad Jafar (Journal of Governance and Social Policy, 2023)
This study aims to analyze the Indonesian Ministry of Internal Affairs' communication patterns on Twitter social media accounts. The research method used is social media analysis (Twitter) @kemendagri. It aims to analyze and measure publication intensity and identify trends and communication patterns of the Ministry of Internal Affairs through its Twitter account. The analytical tool in this study uses Nvivo 14 Plus. The results showed an increasing trend in the tweet intensity of the @kemendagri account in the first four quarters (April 2019 March 2020). Coordination, regulation, decentralization, and integration are the most frequently written samples of tweets. Two hashtags are most often included in the tweet of the @kemendagri account, namely #kemendagri and #infokemendagri. the word that appears most often is "Praja." "Praja" is a word to greet the audience or people who follow the Twitter account @kemendagri. There have been concrete efforts to integrate promotion through social media with a decentralized approach, in which the Ministry of Internal Affairs has given local governments the freedom to actively contribute to managing the Twitter account. This decentralized approach illustrates Ministry of Internal Affairs commitment to empowering local governments and increasing their participation in government communication processes.